Determination of the antimicrobial capacity of melissa officinalis leaves against the strain escherichia coli for application in fresh type cheese - Rojas Vallejo, María Fernanda; Rojas Vallejo, Hernán Alexander; Uvidia Fassler, María Isabel; Almeida Castro , Alexandra Cristina (Tierra Infinita, 2024)
Nowadays, plant extracts are increasingly used in the formulation of food products due to their antimicrobial capacity, which combats pathogenic strains that can compromise food quality. This research evaluated the antimicrobial effect of dried leaves of Melissa officinalis on the Escherichia coli strain, determining the Minimum Inhibitory Concentration (MIC) through an aqueous extract of the plant. More pronounced inhibition zones were observed at concentrations of 1.5% and 2%. The most effective concentrations were used in the production of fresh cheeses, incorporating dried leaves of Melissa officinalis during the curdling and draining stages. This allowed the extraction of the active compounds from the plant, integrating them into the cheese. The physicochemical characteristics of these cheeses were compared with a control sample (cheese without the addition of leaves). When adding the dried leaves of Melissa officinalis, the parameters of acidity, pH, protein and fat did not show significant differences compared to the control sample. However, significant differences were found in moisture content: cheeses with 1.5% and 2% leaves showed a reduction in water content, decreasing from 61.25% in the control to 55.16% when incorporating dry leaves.